2022
DOI: 10.1007/s10488-022-01204-3
|View full text |Cite
|
Sign up to set email alerts
|

“These are people just like us who can work”: Overcoming clinical resistance and shifting views in the implementation of Individual Placement and Support (IPS)

Abstract: Purpose Individual Placement and Support (IPS) is a recovery-based approach to support people with mental health difficulties back into employment. Embedding of IPS within the mental health Multi-Disciplinary Team (MDT) is a key component of IPS fidelity; however, few studies have examined how those involved with IPS implementation navigate this process. This article explores how IPS Employment Specialists (ES) and Occupational Therapist (OT) Managers integrated and embedded IPS within traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Zero exclusion is thus in line with the 'environmental turn' (Tøssebro 2004), emphasising that it is the environment that must change to successfully (re-)integrate individuals experiencing mental health conditions into the labour market. However, like Bonfils (2020) and Sharek et al (2022), this study has shown that working by the zero-exclusion principle is challenging.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Zero exclusion is thus in line with the 'environmental turn' (Tøssebro 2004), emphasising that it is the environment that must change to successfully (re-)integrate individuals experiencing mental health conditions into the labour market. However, like Bonfils (2020) and Sharek et al (2022), this study has shown that working by the zero-exclusion principle is challenging.…”
Section: Discussionmentioning
confidence: 77%
“…This is because an individual's interest in working has shown to be a more significant predictor of success than assessments of job readiness conducted by professionals (Becker et al 2015: 68). Despite the political goal of prioritising opportunities over limitations, it has proven challenging to effectively achieve this, as shown in IPS implementation studies (e.g., Bonfils 2021;Sharek et al 2022). This is supported by research on welfare frontline workers, who were found to maintain a 'deficit approach'.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On this note, the use of Action Research to help implement evidence-based practices in service reform and complex change may be one method for those on the ground to consider [ 94 ]. Using action research to surface challenges during the implementation of TIC in real time and delivering this data to implementation groups on the ground has been found to be successful in managing complex change in healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…A national programme supports the roll-out of IPS, built on a partnership model between employment support organisations and the The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/2398-8819.htm mental health services, and guided by the National IPS Steering Group. Sharek et al (2022) explored how IPS was integrated and embedded within the Irish context.…”
Section: Introductionmentioning
confidence: 99%